Static and Dynamic Compressive Stress-Strain Behavior of Recycled Tire Crumb Rubber Mortar - Yang, Manjuan; Guo, Zhongyin; Zhang, Wenhua; Chen, Guangming; Zhang, Liwen (Frontiers in Materials, 2020)
Crumb rubber mortar (CRM) made from scrap tires can be used in highway, high-speed railways, and airport pavements as a structural material, which may help solving the problems of raw material shortage and waste tire pollution at the same time. To develop it, a systematic study of the stress-strain behavior of CRM under static and dynamic compression is therefore very important. In this paper, the CRM specimens containing four different contents of crumb rubber (5%, 10%, 15%, 20%) and four different rubber particle sizes (30 mesh and 50 mesh, 60 mesh, 80 mesh) were prepared to study the workability of fresh CRM and the stress-strain curve of hardened CRM under static compression and dynamic compression. The result shows that the fluidity of CRM decreases obviously with the addition of crumb rubber and the increase of fine particle rubber size. The CRM, when the incorporating crumb rubber increased in the mortar, presented a decrease in its static compressive strength and modulus of elasticity, but an increase in its critical strain and compressive toughness. The CRM also showed an obvious strain rate effect. When the incorporated rubber contents remained constant, the CRM increased its dynamic compressive strength and DIF with the increase of strain rates. Similar to that in the static compressive test, the addition of crumb rubber has a positive effect in enhancing the deformation and energy absorption properties under dynamic impact loading.